Heterogeneous university research and firm R&D location decisions: research orientation, academic quality, and investment type - René Belderbos; Nazareno Braito; Jian Wang (The Journal of Technology Transfer, 2024)
Universities play an important role in regional development and innovation and engage with the industry through various channels. In this paper, we examine the role of heterogeneous characteristics of university research, in particular universities' orientation towards basic or applied research and the quality of this research, in attracting firms' R&D investment. We analyze the location decisions in the United States by foreign multinational firms at the level of metropolitan areas. We contrast research and development projects and explore whether they are driven by different factors. We find that the drivers of location choice differ importantly as a consequence of the type of the focal R&D investment of the firm. Universities with an orientation towards applied scientific research and exhibiting higher academic quality of applied research attract more R&D investment focusing on development activities. In contrast, firms' investments in research activities are attracted by the academic quality of basic scientific research of local universities. Hence, increased university emphasis on academic engagement and applied research may have negative consequences for industrial research in the region.
Keywords: F21; F23; O32; 600; Location choice; R&D FDI; Industry science links; Basic and applied research; Academic quality